Chocojar4u / Fatin Nur Ellyssa Rosli and Nur Balqis Syafiah Abdul Rahman - Rosli, Fatin Nur Ellyssa; Abdul Rahman, Nur Balqis Syafiah (2023)
Once, there is magic inside a box, but now our magic is inside a jar. With a powerful taste of chocolate! "Yummy to the Last Bite" is a tagline for Chocojar4u that represents our beloved customers. The main objective for the business is to offer a good quality snack (Chocojar) with premium chocolate with affordable and reasonable prices. We started our online business early this year on 16 April 2023 using social media platforms which is Facebook Page. As an admin of our page, it is our responsibility to update all the information regarding promotion of the products, posting the advertisement, comments and answering on customer’s questions and feedback posting from the customers. Besides, it is also responsible for us to build a networking and relationship with customers on social media. Our targeted customers are people especially around UiTM Puncak Alam, Selangor. Since our first launching, we received a lot of good feedback from the customer regarding the quality, the taste, the packaging and also the price. We do offer delivery service with charge to those who are near to our area. Due to the good feedback, increasing demands for our products results into a good profitable sale revenue to our business project. Therefore, Chocojar4u is a good marketable product of choice that can be further expanded to many different areas as the business keeps on growing even above our expectations.